Microeconomics - Gravelle, Hugh; Rees, Ray (Pearson Education, 2004)
"The book begins at the intermediate level and ends at a level appropriate for the graduate student. Updated and revised, this is a new edition of one of the best-selling advanced microeconomics texts to be published in Europe. This well informed book provides a comprehensive exposition of modern microeconomic theory, covering many of the issues currently being researched and debated. The book offers very rigorous, mathematical treatment of the topics discussed making it appropriate for graduate as well as able intermediate level students. The writing style is clear and concise and the book is particularly liked for the thoroughness with which the concepts are dealt."--Provided by publisher.